The prognostic value of TP53 and its correlation with EGFR mutation in advanced non-small cell lung cancer, an analysis based on cBioPortal data base. (September 2018) - Jiao, Xiao-Dong; Qin, Bao-Dong; You, Pu; Cai, Jian; Zang, Yuan-Sheng
Highlights: The prognostic value of TP53 in advanced NSCLC is poorly reported. TP53 mutation was a negative prognostic factor for overall survival in advanced NSCLC. Different mutation type of TP53 could predict different OS in advanced NSCLC. Abstract: Objectives: The prognostic value of TP53 in advanced non-small-cell lung cancer (NSCLC) is unclear. Whether different mutated exon has different prognostic value is unknown. We sought to reveal the prognostic value of TP53 in advanced NSCLC, as well as the correlation with EGFR mutation. Materials and Methods: Information regarding TP53 and EGFR alterations and patients' survival time in advanced NSCLC was downloaded from the Cancer Genome Atlas Database. We further subdivided TP53 and EGFR mutation into subgroups based on different mutation exon, and then evaluated the distribution of different mutation exon as well as the prognostic value. Results and Conclusion: Overall, 1441 pieces of data from 1441 metastatic NSCLC patient were collected. Mutation rate of TP53 was 56.1% (809/1441). TP53 mutation was a negative prognostic factor for OS. The estimated survival time for wild type TP53 and mutated TP53 was 27.0 months (95% CI, not reached) and 19 months (95% CI, 16.62 to 21.38), respectively, (p < 0.001). We divided TP53 mutations into 4 groups, OS in these 4 groups was 27 months (95% CI, not reached), not reached, 21 months (95% CI, 17.16 to 24.84) and 13 months (95% CI, 10.39 to 15.61). The difference was statistically significant (p < 0.001). Patients with EGFR exon 19/21 or non-exon 19/21 mutation demonstrated a higher rate of mutated type TP53 than EGFR wild type patients. Survival curve in EGFR wild type patients indicated that TP53 wild type patients had the best prognosis. In patients with exon 19/21 mutated EGFR, the trend was the same (P < 0.001).TP53 mutation is a negative prognostic factor in advanced NSCLC, different mutated exon has different prognostic value. When coupled with EGFR mutation, we can predict the prognosis of advanced NSCLC patients more accurately.